Pain and Communication in Children with Cerebral Palsy: Influence on Parents’ Perception of Family Impact and Healthcare Satisfaction - Riquelme, Inmaculada (Children (Basel), 2021)
Cerebral palsy (CP) is an impacting chronic condition. Concomitant comorbidities such as pain and speech inability may further affect parents’ perception of the pathology impact in the family quality of life and the provided care. The objective of this cross-sectional descriptive correlational study was to compare parental reports on family impact and healthcare satisfaction in children with CP with and without chronic pain and with and without speech ability. Parents of 59 children with CP (age range = 4–18 years) completed several questions about pain and speech ability and two modules of the Pediatric Quality of Life Measurement Model: The PedsQLTM 2.0 Family Impact Module and the PedsQLTM Healthcare Satisfaction Generic Module. Our findings revealed that children’s pain slightly impacted family physical health, social health and worry. In children without pain, speech inability increased the perceived health impact. Parents’ healthcare satisfaction was barely affected by pain or speech inability, both increasing parents’ satisfaction in the professional technical skills and inclusion of family domains on the care plan. In conclusion, pain and speech inability in children with CP can impact family health but not healthcare satisfaction. Regular assessment and intervention in family health is essential for the design of family-centred programs for children with CP.